The time traveler's guide to Elizabethan England - Mortimer, Ian, 1967- (Viking, 2013)
" ... this popular history explores daily life in Queen Elizabeth's England, taking us inside the homes and minds of ordinary citizens as well as luminaries of the period, including Shakespeare, Christopher Marlowe, Sir Walter Raleigh, and Sir Francis Drake. Organized as a travel guide for the time-hopping tourist, Mortimer relates in delightful (and occasionally disturbing) detail everything from the sounds and smells of sixteenth-century England to the complex and contradictory Elizabethan attitudes toward violence, class, sex, and religion. Original enough to interest those with previous knowledge of Elizabethan England and accessible enough to entertain those without, The Time Traveler's Guide is a book for Elizabethan enthusiasts and history buffs alike."--